2022
DOI: 10.1007/s13730-022-00702-5
|View full text |Cite
|
Sign up to set email alerts
|

A de novo case of minimal change disease following the first dose of the Moderna mRNA-1273 SARS-CoV-2 vaccine without relapse after the second dose

Abstract: In recent times, new onset or relapse of nephrotic syndrome following the first dose of SARS-CoV-2 vaccines has been reported. Although the vaccination could trigger nephrotic syndrome, the question of whether the same vaccine should be administered as the second dose remains unanswered. A 25-year-old woman had taken the Moderna mRNA-1273 SARS-CoV-2 vaccine (mRNA-1273) and 26 days later, she noticed facial and peripheral edema. One week later she was referred and admitted to our hospital, wherein laboratory te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…[ 3 , 53 ] Many studies proposed that there could be aberrant activation of the immune system in genetically susceptible individuals,[ 20 ] causing a dysregulated T-cell response. [ 15 , 16 , 45 ] This was found to cause alterations in glomerular permeability due to the production of glomerular permeability factor, causing diffuse foot process effacement. [ 16 ] This eventually leads to T-cell-mediated podocyte injury.…”
Section: W Hat Are the P Ossible ...mentioning
confidence: 99%
See 4 more Smart Citations
“…[ 3 , 53 ] Many studies proposed that there could be aberrant activation of the immune system in genetically susceptible individuals,[ 20 ] causing a dysregulated T-cell response. [ 15 , 16 , 45 ] This was found to cause alterations in glomerular permeability due to the production of glomerular permeability factor, causing diffuse foot process effacement. [ 16 ] This eventually leads to T-cell-mediated podocyte injury.…”
Section: W Hat Are the P Ossible ...mentioning
confidence: 99%
“…Conversely, Mochizuki et al . [ 15 ] reported a case of de novo minimal change disease in a 25-year-old woman after the first dose of Moderna mRNA-1273 vaccination, which had complete remission following steroid therapy. They have also found that there is no relapse of renal complications following second dose vaccination and suggested that it may be safe to administer the subsequent dose vaccination alongside immunosuppressive treatment to achieve complete remission of renal complications developed.…”
Section: S I T S Afe To ...mentioning
confidence: 99%
See 3 more Smart Citations